2020
DOI: 10.1074/jbc.ra120.014371
|View full text |Cite
|
Sign up to set email alerts
|

FmhA and FmhC of Staphylococcus aureus incorporate serine residues into peptidoglycan cross-bridges

Abstract: Staphylococcal peptidoglycan is characterized by pentaglycine crossbridges that are crosslinked between adjacent wall peptides by Penicillin-Binding Proteins (PBPs) to confer robustness and flexibility. In Staphylococcus aureus, pentaglycine crossbridges are synthesized by three proteins: FemX adds the first glycine and the homodimers FemA and FemB sequentially add two Gly-Gly dipeptides. Occasionally, serine residues are also incorporated into the crossbridges by enzymes that have heretofore not been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
(98 reference statements)
2
16
0
Order By: Relevance
“…This notion is substantiated by cell cycle analysis demonstrating that AEA treatment leads to an accumulation of bacteria in the G2/M phase. When studying the expression of genes associated with cell division, we observed significant upregulation of ftsZ , ftsA , and divIB that are important for proper function of the divisome 49 , while the autolytic hydrolases lytM , lytN and lytA important for daughter cell separation 50 were downregulated by AEA. The increase in the cell division genes might be a compensatory mechanisms to the bacteriostatic effect of AEA, and might facilitate the resumption of cell growth at later time points.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This notion is substantiated by cell cycle analysis demonstrating that AEA treatment leads to an accumulation of bacteria in the G2/M phase. When studying the expression of genes associated with cell division, we observed significant upregulation of ftsZ , ftsA , and divIB that are important for proper function of the divisome 49 , while the autolytic hydrolases lytM , lytN and lytA important for daughter cell separation 50 were downregulated by AEA. The increase in the cell division genes might be a compensatory mechanisms to the bacteriostatic effect of AEA, and might facilitate the resumption of cell growth at later time points.…”
Section: Discussionmentioning
confidence: 95%
“…In light of our finding showing that AEA affects the bacterial growth, we also examined the expression of cell division-associated genes. AEA caused a two-fold increase of the ftsZ, ftsA and divIB that form part of the divisome 49 , while the expression of the hydrolase enzymes lytM, lytN and lytA important for daughter cell separation 50 were significantly repressed (Fig. 7D).…”
Section: Effect Of Aea On Gene Expressionmentioning
confidence: 99%
“…lyrA was first identified in a screen for mutants resistant to lysostaphin, an endopeptidase that cleaves the pentaglycine cross bridge that cross-links S. aureus peptidoglycan (11). Pentaglycine cross bridges are synthesized on the cis side of the plasma membrane by the Fem factors and LyrA does not play a direct role in this process (11,(23)(24)(25)(26). lyrA was later found in a screen for mutants deficient in surface display of SpA, an abundant substrate of sortase A that is covalently attached to pentaglycine cross bridges; the gene was dubbed spdC (12).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, SagB pulldown experiments identified LyrA as well as FemA, FemB, FmhC, SecDF, and SecA. FemA and FemB form homodimers that sequentially add two Gly-Gly dipeptides to the peptidoglycan cross bridge, whereas FmhC pairs with FemB to incorporate Gly-Ser dipeptides into cross bridges (23)(24)(25)(26). These proteins are enriched at the septum, the site of peptidoglycan assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The five ORFs were not found in the genomic sequences of strains that harbor spm23_A but not spm23_B; thus, we concluded that spm23_B was inherited together with the five ORFs, and called it the "spm23_B cluster. " spm23_B is located near a gene encoding an aminoacyl transferase that displays similarity to FmhA, which is reported to be involved in the incorporation of serine residues into S. aureus peptidoglycan cross-bridges (Willing et al, 2020), as well as genes encoding the Epr and Lif proteins, known to provide resistance to Ale-1 and Lss in S. capitis and S. simulans, respectively (Sugai et al, 1997b;Thumm and Gotz, 1997; Supplementary Table 4).…”
Section: Spm23_b Forms Part Of a Genetic Cluster Related In Function To Peptidoglycan Metabolismmentioning
confidence: 99%